Schermo delle mie brame. Lyotard e un cinema che si chiama desiderio (Materiali di Estetica. Terza serie, 2014)
In the early 1970s, Jean-François Lyotard stated that “a true mutation of desire” is at work in our epoch and began to explore this mutation in cinema too. Through specific reference to Jacques Lacan’s “mirror stage” theory, Lyotard suggested that the cinematic screen can be considered as a kind of social mirror. Also, he linked the contemporary mutation of desire to a possible mutation of the role of the cinematic screen as a surface to make seen. Critically discussing these points, I argue that we may connect the XXth century – meant as the century of cinema – to a progressive affirmation of a different way of conceiving the giving of the true. Such a way shall slip from a theatrical apparatus (that is, par excellence, a representative apparatus opening up through the opening of a curtain) to a sort of cinematographic apparatus. KEYWORDS: cinema; desiderio; schermo; visione